Three Steps Towards the Phenomenology of Literature with Arūnas Sverdiolas - Levina, Jūratė (Problemos, 2020)
The paper outlines the methodological orientation of Arūnas Sverdiolas’s scholarship and his school towards the praxis of the hermeneutic understanding of concrete cultural phenomena and takes this approach into the field of the phenomenology of literature. The attempt begins with a definition of the literary work in the hermeneutic framework of discourse, in which the work is considered to be an utterance that expresses an originary grasp of world phenomena. This capacity of the work to express is enabled by the operative mechanism of discourse, which binds, by the means of grammar and reference, the linguistic form of the work to the intentional structure of experience. To show this mechanism at work, the paper looks into Alfonsas Nyka-Niliūnas’s project of self-creation: Sverdiolas examines the poet’s diaries to reconstruct his effort of cultivating his poetic ego along the hermeneutic lines of the existential time, while Nyka-Niliūnas himself expresses this self-conception poetically as a more general phenomenon – the phenomenon of poetic self-consciousness as such – in the poem “Autobiography 1986”.
Keywords: literatūros fenomenologija; literatūros hermeneutika; literatūrinis diskursas; Arūnas Sverdiolas; Alfonsas Nyka-Niliūnas